The genesis of training in landscape architecture in Portugal - Ana Catarina Antunes; Teresa Portela Marques; Teresa Andresen (Projets de Paysage)
This article discusses the origin of Landscape Architecture in Portugal. It focuses, above all, on the principles of the Landscape Architecture course that Francisco Caldeira Cabral (1908-1992) launched at the Higher Institute of Agronomy, Technical University of Lisbon, in the early 1940s, with a clear influence on what he learned and experienced at the Berlin Agricultural College where he graduated in the late 1930s. To better understand the foundations behind the creation of the degree in Portugal it is necessary to look back to the 19th century in Prussia and learn about the scientific-pedagogical program of the Royal Gardeners Training School (Königliche Gärtnerlehranstalt) and the Berlin Agricultural College (Landwirtschaftliche Hochschule Berlin) founded in 1929 and considered the successor of that gardeners’ School. The texts and works of Caldeira Cabral, as a student and later as a teacher, were also of primordial importance. This study was developed having as basis recent research carried out on the German influence in the genesis of Landscape Architecture in Portugal. It made use, mainly, of primary sources of information, either published or unpublished files, accessed in public and private archives. Also, documents on the education of Caldeira Cabral in Berlin and on the first years of the Landscape Architecture degree were analysed.